- 445

- 0

**1. Homework Statement**

Use the method of dimensional analysis to show that the functional dependence in equation (1) can be derived from an observational expression: [TEX]lambda = k*mu*f^m*T^n[/TEX].

**2. Homework Equations**

[TEX]lambda=k\sqrt {{\frac {T}{\mu}}}{f}^{-1}[/TEX] (1)

[TEX]lambda = k*mu*f^m*T^n[/TEX]

[TEX]\mu={\frac {{\it kg}}{m}}[/TEX]

[TEX]T={\frac {{\it kg}\,m}{{s}^{2}}}[/TEX]

**3. The Attempt at a Solution**

First I solve for n.

[TEX]m={\frac {{m}^{n}}{m}}[/TEX]

n = 2

Now I solve for m.

[TEX]0=0={1/s}^{m}{s}^{-2\,n}[/TEX]

m = -4

so now I have:

[TEX]\lambda={\frac {ku{T}^{2}}{{f}^{-4}}}[/TEX]

I don't understand what the question means by "show that the

*in equation (1). . ."*

**functional dependence**In equation (1) we were told that [TEX]\lambda[/TEX] and T were variables. Well in equation I've derived [TEX]\lambda[/TEX] and T could very well be variables, but I don't think I understand the question. But, if the question is asking me to equate the two expressions and prove an "identity", then I can't do that. Any help welcomed and appreciated.

When I try to "work" the units out they don't work out at all.